A PHOTOELASTIC STUDY OF STRESSES IN THE FEMURE - Jamal A. Hassan; Sadiq J. Abass; Zainabmajid (Journal of Madenat Alelem University College, 2018)
The femur bone is the longest bone in the human body. The proximal end of femur contacted at hip joint and in the distal end contacted at knee joint. Femur bone affected with muscles attached with it and with contacts at joints and weight bearing of body, all of these applied loads on femur and stresses effect result. In this study we will discuss stress analysis on the femur bone when a compressive load applied on  the head of the bone at the contact region with acetabulum by using the photo elasticity transmission technique. The normal femur bone scaling to prototype according to material properties an polariscope load applied. The effect of load on the prototype with passage of polarized light through it give fringes pattern which Interpretation to show the stress at head of femur and at the shaft of femur. The study was done in Baghdad during 2016 from Al-Nahrain University.